2022
DOI: 10.1051/0004-6361/202142979
|View full text |Cite
|
Sign up to set email alerts
|

Decayless longitudinal oscillations of a solar filament maintained by quasi-periodic jets

Abstract: Context. As a ubiquitous phenomenon, large-amplitude longitudinal filament oscillations usually decay in 1–4 periods. Recently, we observed a decayless case of such oscillations in the corona. Aims. We try to understand the physical process that maintains the decayless oscillation of the filament. Methods. Multiwavelength imaging observations and magnetograms were collected to study the dynamics of the filament oscillation and its associated phenomena. To explain the decayless oscillations, we also performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…In the example on the top panel of Fig. 11 we do observe, similar to Ni et al (2022), oscillations without decay, but also find clearly disrupted oscillatory behaviour. There is hence no clear dependence of observed periods with the interpulse interval of the pulses that we can infer.…”
Section: Counter Streams and Oscillationssupporting
confidence: 71%
See 1 more Smart Citation
“…In the example on the top panel of Fig. 11 we do observe, similar to Ni et al (2022), oscillations without decay, but also find clearly disrupted oscillatory behaviour. There is hence no clear dependence of observed periods with the interpulse interval of the pulses that we can infer.…”
Section: Counter Streams and Oscillationssupporting
confidence: 71%
“…It seems that for some threads the flows support and contribute positively to the oscillations, while for others the flows change their initial trajectory and disturb the threads from their expected oscillatory behaviour. In a recent paper by Ni et al (2022) the authors analysed decayless oscillations of a filament observed near an active region on July 5, 2014. They conjecture that the decayless oscillations are caused by quasiperiodic jets happening as a result of intermittent reconnection at the footpoints of the flux rope supporting the filament.…”
Section: Counter Streams and Oscillationsmentioning
confidence: 99%
“…However, in our observations it appears that several small flares produced the amplification. Ni et al (2022) found evidence of periodic triggering of large-amplitude oscillations by quasi-periodic jets producing decayless oscillations. A similar phenomenon might amplify the oscillations when the oscillation periods and triggering are in resonance.…”
Section: Oscillation Triggermentioning
confidence: 98%
“…For the former, the length and dynamics of filament threads can indicate the structure of the supporting magnetic dip Zhou et al 2014;Guo et al 2021bGuo et al , 2022; the filament morphology, including aspect ratio, the composition of threads, and the horn and cavity can show the twist degree of a flux rope (Guo et al 2021a(Guo et al , 2022; the filament barbs may indicate the bifurcations of a flux rope due to parasitic polarities in the surrounding environment (Aulanier & Demoulin 1998), and the fibrils in a filament channel can be used to determine the chirality of the filament (Martin 1998). As for the filament oscillation, longitudinal oscillations have been widely applied to derive the curvature radius of local field lines Zhang et al 2012Zhang et al , 2013Zhang et al , 2020Zhou et al 2017Zhou et al , 2018Ni et al 2022), and transverse oscillations can be utilized for the estimate of the magnetic-field strength around the filament (Shen et al 2014;Zhou et al 2018).…”
Section: Filament Drainage Sites: the Hint To Reflect Flux Rope Struc...mentioning
confidence: 99%